PERAN KOMITMEN ORGANISASIONAL MEMEDIASI PENGARUH BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Setyawan, I Putu Gede Ari; Sriathi, Anak Agung Ayu (E-Jurnal Manajemen, 2020)
The purpose of this study was to determine the role of organizational commitment in mediating the influence of organizational culture on organizational citizenship behavior (OCB). This research was conducted at the Investment Office and PTSP in Badung Regency. The number of samples used in this study were 135 employees. The sampling technique is done by saturated sampling. The analysis technique used is path analysis. The results showed that organizational culture had a positive and significant effect on organizational citizenship behavior (OCB), organizational culture had a positive and significant effect on organizational commitment, organizational commitment had a positive and significant effect on organizational citizenship behavior (OCB), and organizational commitment positively and significantly mediated culture organization of organizational citizenship behavior (OCB) at the Badung Regency Investment and PTSP Office. Efforts to improve organizational citizenship behavior (OCB) on employees, organizations should be able to improve organizational culture by increasing calm in the work environment. Keywords : Organizational Culture, Organizational Commitment, Organizational Citizenship Behavior (OCB).